Implementation of cyber counseling in the Merdeka Belajar curriculum in the era of society 5.0 - Arianti, Alivia Eka; Hidayah, Nur; Wahyuni, Fitri (Journal of Research in Instructional, 2023)
Counselors have an important role in the success of the Merdeka Belajar curriculum. Counselors need to have cyber counseling  to support their professionalism in implementing guidance and counseling. This study aims to examine the implementation of cyber counseling  in the Merdeka Belajar curriculum. The research uses the systematic literature review method which is carried out in six stages, namely problem formulation, systematic literature search, screening and selection of relevant articles, qualitative analysis and synthesis, quality control, compiling reports. A total of 14 articles that passed the screening were reviewed to identify various strategies that have been used for implementation. The results of this study indicate that the implementation of cyber counseling  in Merdeka Belajar curriculum includes technical preparation of hardware and software. The stages that need to be considered are almost the same as counseling in general. First, the preparation stage which includes technical preparation of hardware, software, and evaluation. Second, the counseling process stage which consists of delivery, exploration, interpretation, coaching, and assessment. And the third stage, the post-counseling stage which is marked by the success of counseling with effective client conditions. This research can be a reference for further research to be able to develop more innovative and applicable cyber counseling  implementation strategies.